Clinical Reasoning: A 12-Month-Old Male Child With Staring Episodes, Ataxia, and Right-sided Weakness. (1st November 2022) - Brosius, Stephanie N.; Otto, William; Waldman, Amy; Russo, Michael; McGuire, Jennifer
Abstract : Baylisascaris procyonis, or raccoon roundworm, is a rare cause of eosinophilic meningoencephalitis with historically poor clinical outcomes. Symptoms of neural larval migrans begin approximately 2–4 weeks after ingestion with fatigue, nausea, fever, and lethargy and then rapidly progress to weakness, incoordination, ataxia, seizures, altered mental status, and finally coma. Only 31 other cases of CNS Baylisascaris neural larval migrans have been reported, with more than 25% being lethal. Of the remaining cases, all but 3 were neurologically devastated largely because of delays in diagnosis and treatment. We present a case of an infant with Baylisascaris neural larval migrans manifested as right hemiparesis, ataxia, and cortical blindness. Eosinophilia was missed at an outside hospital due to misidentification of eosinophils as monocytes on automated cell differential. Repeated testing of serum and CSF revealed marked eosinophilia consistent with eosinophilic meningoencephalitis, and serum antibody testing through the Centers of Disease Control confirmed Baylisascaris infection. Notably, this child had a remarkably positive outcome with near complete recovery of neurologic function after treatment with albendazole and steroids. Although eosinophilic meningoencephalitis is rare, accounting for less than 3% of all lumbar punctures with pleocytosis, this case illustrates (1) the importance of early disease recognition and treatment to improve patient outcomes and (2) the fact that automated cell differentials may misidentify eosinophils as monocytes.